Performance Analysis on Licensure Examination for Teachers among BEEd Graduates in DOrSU-San Isidro Campus, Philippines - Bugwak, Elven Ruelo (FKIP Universitas Lampung, 2023)
Performance Analysis on Licensure Examination for Teachers among BEEd Graduates in Dorsu-San Isidro Campus Objective: This quantitative research study aimed to explore the Licensure Examination for Teachers results specifically compare the LEPT performances between graduates from AY 2017-2018 and AY 2018-2019, and to the national passing rate . Methods: This study employed made use of the analytical method of research, and documentary analysis of data taken from the official results of LEPT released by the Professional Regulatory Commission (PRC) in the years 2017-2022. In addition, this study made use of frequency counts and percentage to describe the profile of LEPT takers. On the other hand, percentage was used in reporting the average or rating of graduates in their licensure examination. Moreover, T-Test was used to examine the significant difference in the LEPT performances between graduates from AY 2017-2018 and AY 2018-2019. Findings: When compared to national passing rate, results show that DOrSU performed best in September 2021. On the other hand, DOrSU performed low in March 2022. Also, the results from the t-test for equality of means show that there is no significant difference between the AY 2017-2018 and AY 2018-2019 in terms of their ratings in LEPT. Conclusions: It is recommended that schools should create a mechanism in monitoring the performances of their graduates in their licensure examination. Keywords: Teacher education, performance analysis, analytical method of research, documentary analysis.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202325